Effects of Particle Size and Compaction Pressure on the Physical and Energy-Related Properties of Biopellets from Casuarina Equisetifolia - Khamdi Mubarok; Teguh Prasetyo; M. Abdul Ghoni (International Journal of Science, Engineering, and Information Technology, 2025)
The increasing demand for renewable energy requires alternative resources to reduce fossil fuel dependency and mitigate climate change. Biomass has emerged as a promising solution due to its wide availability and favorable combustion characteristics. Casuarina equisetifolia, a fast-growing coastal species abundant in Indonesia, remains underutilized despite its potential as a bioenergy feedstock. This study investigates the effects of particle size variation (20, 40, and 60 mesh) and compaction pressure (2, 3, and 4 tonf) on the quality of biopellets produced from Casuarina equisetifolia. Biomass powder was mixed with 10% tapioca binder, compacted using a hydraulic press with a cylindrical mold, and oven-dried at 150 °C for 30 minutes. Pellet quality was evaluated through moisture content, density, and calorific value following SNI standards. The data were statistically analyzed using two-way ANOVA. The ANOVA results confirmed that both particle size and compaction pressure had significant effects (p 0.05) on all response variables. Moisture content decreased with finer particles and higher pressure, with the lowest value of 5.27% obtained at 60 mesh and 4 tonf. Density increased under the same conditions, reaching 1.191 g/cm³. Calorific value also varied significantly, with the maximum of 4697 cal/g observed at 20 mesh and 4 tonf. These findings demonstrate that optimization of particle size and compaction pressure is essential to improve both physical and energy-related properties of biopellets. The results highlight the potential of Casuarina equisetifolia as a sustainable biomass feedstock to support Indonesia’s Net Zero Emission 2060 target.